2020
DOI: 10.1155/2020/8897441
|View full text |Cite
|
Sign up to set email alerts
|

Frequency Spectrum and Wavelet Packet Analyses of Blasting Vibration Signals for Different Charge Structures in Blasting Peripheral Holes

Abstract: Based on the blasting principle of the cutting seam cartridge, smooth blasting with the charge structures of the usual cartridge and cutting seam cartridge has been designed and implemented, respectively, for different peripheral holes in the same face. Meanwhile, the blasting vibration has been monitored. Through the analysis of the frequency spectrum of blasting vibration signals, it is found that the maximum blasting vibration velocity of the cutting seam cartridge charge is lower than that of the usual car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Chen et al [2] suggested that the altitude magnification effect is caused by the "whipping effect," as the main frequency of the blast wave load is equal to the natural vibration frequency of the bench. Guo et al [3], Soltys et al [4], and Man et al [5] combined theoretical analyses with field tests and confirmed the "slope effect" for both negative and positive slopes, leading to an increase in the slope blast vibration velocity. Qiu [6] considered the rock slope as a multilayered environment and suggested that the blast waves would be superimposed by refraction and reflection after propagating to the interfaces of different layers.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [2] suggested that the altitude magnification effect is caused by the "whipping effect," as the main frequency of the blast wave load is equal to the natural vibration frequency of the bench. Guo et al [3], Soltys et al [4], and Man et al [5] combined theoretical analyses with field tests and confirmed the "slope effect" for both negative and positive slopes, leading to an increase in the slope blast vibration velocity. Qiu [6] considered the rock slope as a multilayered environment and suggested that the blast waves would be superimposed by refraction and reflection after propagating to the interfaces of different layers.…”
Section: Introductionmentioning
confidence: 99%